Factors Influencing Consumer Preferences for Locally Produced Food: a Comparison between Traditional and Modern Markets - Arsil, Poppy; Eddy Sularso, Kusmantoro; Mulyani, Altri (International Journal of Engineering and Technology, 2018)
Traditional and modern markets are both potential distribution channels for the distribution of locally produced food in Indonesia. The aim of the current study is to gain insight into consumer preferences for locally produced food when shopping at both markets. A total of 300 respondents were interviewed using stratified purposive sampling in traditional markets and supermarkets in Banyumas regency. Factor analysis was used to group consumer towards their preferences for local food. The overall KMO values were 0.746 for consumers who shopped in traditional markets and 0.835 for those who purchased locally produced food in modern markets, with a significance level of 0.000 for both segments of consumers. All individual MSAs also emerged as over 0.06. The results show that consumer preferences for locally grown products are very similar in both markets. Five factors were found considerably to influence consumer preferences in both markets, namely habit, food quality, product availability, the tendency to support local food, and the availability of information and knowledge. What makes the difference between markets is that supermarket shoppers have enthusiasm and proud eating local food product. The total variance for the six factors was 64.245% and 65.705% for traditional and modern markets, respectively.Â Â